Satisfacción laboral y su influencia en el compromiso organizacional de los trabajadores de la Cooperativa de Ahorro y Crédito Parroquia San Lorenzo - La Libertad, 2019. - Perez Barrenechea, Lourdes Gabriela (2019)
ABSTRACT The present research entitled "Job satisfaction and its influence on the organizational commitment of the workers of the Cooperativa de Ahorro y Crédito Parroquia San Lorenzo - La Libertad, 2019", aimed to determine how job satisfaction influences the organizational commitment of workers of the Cooperativa de Ahorro y Crédito Parroquia San Lorenzo - La Libertad, 2019. This was achieved thanks to the use of two questionnaires: S20 / 23 of Meliá and Peiró for the first, and the questionnaire of Meyer and Allen for the second, which They were applied to 82 workers. Through the Chi Square test, it was determined that the level of job satisfaction significantly influences the level of organizational commitment of the workers in the San Lorenzo Parish Savings and Credit Cooperative (p = 0.000 <0.05). Through the Stanon Scale, it was determined that the level of job satisfaction and the level of organizational commitment of workers is medium (41.5% and 58.5%, respectively). Finally, using Spearman's rank correlation method, it was concluded that job satisfaction directly and proportionally influences the organizational commitment of workers in the San Lorenzo Parish Savings and Credit Cooperative (rs = 0.615 and p = 0.000 <0.05); In addition, there is a directly proportional and significant relationship between the dimensions of job satisfaction and organizational commitment (p = 0.000 <0.05).